Unlocking the potential of root and tuber crops: the visionary role of the International Potato Center - International Potato Center (2024)
In the face of the rapidly evolving global landscape and climate change, the International Potato Center (CIP) stands tall with a compelling vision and mission. Rooted in the commitment to sustainable agriculture, climate resilience, and improving the quality of life for people in the Global South, CIP's vision and mission are the guiding principles steering the organization through a world marked by uncertainty and change.